Cardiac sarcoidosis presenting as recurrent ventricular tachycardia: a case report - Yasir, Mir (BioMed Central, 2009)
INTRODUCTION: Sarcoidosis is a multi-systemic disorder involving various organ systems. Though cardiac involvement is uncommon it can present as life threatening arrhythmias and sudden death. CASE PRESENTATION: Here we present 27 years old married female with a series of arrhythmias with no initially obvious aetiology. On further evaluation she was diagnosed as having cardiac sarcoidosis. CONCLUSION: Cardiac sarcoidosis is an important cause of death in patients with systemic sarcoidosis. It is therefore necessary to have high index of suspicion when symptoms are present rather than ignoring them.